Simulation of polymer flooding in one of the Iranian oil fields - Mehdi Mohammad Salehi; Abdolvahid Hekmatzadeh; Valy Ahmad Sajjadian; Mohammad Masoumi (Egyptian Journal of Petroleum)
Polymer flooding is the most important enhanced oil recovery (EOR) process, improving the water–oil mobility ratio. Polymers act basically increasing the viscosity of the injected water and reducing the swept zone permeability, allowing an increase in the vertical and areal sweep efficiency of the water injection, and, consequently, increasing oil recovery. In this study, initially based on experimental work the polymer properties were enhanced using the amount of Nano clay to fixed concentration of polymer. Then the polymer flooding was simulated and comparisons were made between obtained results of polymer flooding simulated with water natural depletion and water flooding process in different scenarios. This study shows the optimum concentration of Nano clay could improve polymer properties. Results also show that the polymer flooding scenario has higher oil recovery in comparison to other displacement methods such as natural depletion and water flooding.